Composite corundum-based refractory material with Al-coated AlN coating structure for RH refining furnace
By introducing magnesium-aluminum spinel aggregate, functionalized alumina powder and modification bonding agent into the refractory materials for RH refinery, Al@AlN coated structure composite corundum refractory materials were prepared, which solved the problem of insufficient mechanical properties and thermal shock stability at high temperatures, and achieved better slag iron permeation and erosion resistance and thermal shock stability.
Patent Information
- Application Number
- CN202510635958.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-07-29
- Estimated Expiration
- 2045-05-16
AI Technical Summary
The refractory materials used in existing RH refining furnaces are insufficient in mechanical properties and thermal shock stability at high temperatures, making it difficult to effectively resist slag-iron penetration and erosion.
Magnesium aluminum spinel is used as aggregate, functionalized alumina powder, aluminum nitride powder and metal aluminum powder are used as substrates, and the modification binder magnesium aluminate sol and aluminum phosphate blend are added to prepare Al@AlN coated structure composite corundum refractory material through gradient baking to form MgAlON and dense aluminum magnesium phosphate ceramic phases to improve material performance.
It significantly improves the mechanical properties of refractory materials, resistance to slag-iron penetration and corrosion and thermal shock stability, and enhances the material's thermal shock resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the technical field of refractory preparation, and more specifically, to an Al@AlN-coated composite corundum-based refractory for RH refining furnaces. Background Art
[0002] In modern ironmaking processes, the blast furnace ironmaking process has many advantages such as large production scale, high operating efficiency, low production cost, low fuel consumption, full energy utilization, and mature technology. During the development of the ironmaking industry, it will still occupy a dominant position. Improving production efficiency, reducing production costs, and reducing energy consumption are the core paths for steel enterprises to achieve sustainable development. Against this background, the enlargement of blast furnaces and intensified smelting technologies have become an inevitable choice for the industry's development. While these technological innovations have increased production capacity, they have also put forward revolutionary requirements for the refractory lining, which serves as the "armor protection" of blast furnaces.
[0003] Compared with traditional oxide refractories, non-oxide refractories have excellent erosion resistance, thermal shock resistance, and thermochemical stability, and do not contaminate molten steel. Metal-oxide composite refractories undergo a series of thermochemical reactions during high-temperature applications, in-situ generating non-oxide reinforcing phases, optimizing the composition and microstructure, and transforming into non-oxide-oxide composite refractories, which are expected to achieve good application effects in the RH refining field. Among them, MgAlON has good application prospects in the fields of refractories and high-tech ceramics due to its excellent slag erosion resistance, liquid metal corrosion resistance, and good mechanical properties.
[0004] Pichlbauer et al. used Al2O3, MgO, AlN, and MgAl2O4 as the main raw materials to prepare MgAlON single-phase materials at 1650 °C and 1800 °C respectively, and analyzed the effect of MgO as the magnesium source on the synthesis of MgAlON materials. The research shows that the volume expansion caused by the in-situ generation of MgAl2O4 results in a higher porosity of the materials synthesized with MgO as the magnesium source, reducing the mechanical properties and thermal shock stability of the prepared refractories. Summary of the Invention
[0005] To solve the technical problems mentioned in the background art, this application provides an Al@AlN-coated composite corundum-based refractory for RH refining furnaces.
[0006] An Al@AlN-coated composite corundum-based refractory for RH refining furnaces is prepared by adopting the following technical scheme: Using magnesia-alumina spinel as the aggregate, a mixture of functionalized alumina powder, aluminum nitride powder and metallic aluminum powder as the matrix, adding a modified binder to the mixture of the aggregate and the matrix to obtain a raw material mixture, placing it in a high-temperature furnace under a nitrogen atmosphere, heating to 550 - 660 °C and holding for 4 - 8 h, then placing it at 1560 - 1680 °C and holding for 3 - 5 h, and cooling to obtain an Al@AlN-coated structure composite corundum-based refractory material for RH refining furnaces, wherein the mass ratio of the aggregate, the matrix and the modified binder is 76 - 82:10 - 14:2 - 4.
[0007] Preferably, the magnesia-alumina spinel in the aggregate is one or a mixture of several of fused magnesia-alumina spinel, sintered magnesia-alumina spinel or high-purity magnesia-alumina spinel. The weight fractions of the components of the aggregate are as follows: 15 - 33% of 5 - 3 mm magnesia-alumina spinel particles, 48 - 59% of 3 - 1 mm magnesia-alumina spinel particles and the balance of 1 - 0 mm magnesia-alumina spinel particles. Preferably, in the matrix, the weight fraction of the functionalized alumina powder is 52 - 70%, the particle size of the aluminum nitride powder ≤ 72 µm, the weight fraction of the aluminum nitride powder is 12 - 25% and the balance is metallic aluminum powder. The particle size of the metallic aluminum powder < 65 µm, and the A1 content in the metallic aluminum powder is 99 - 99.9%.
[0008] Preferably, the modified binder is composed of magnesium aluminate sol and aluminum phosphate mixed in a mass ratio of 3:1 - 2.
[0009] Preferably, the functionalized alumina powder is prepared by the following steps: Step A1: Dissolve cationic aluminum salt, sodium metaaluminate and polyethylene glycol in deionized water of equal mass respectively, and stir magnetically for 0.5 - 1 h to obtain a cationic aluminum salt aqueous solution, a sodium metaaluminate aqueous solution and a polyethylene glycol aqueous solution; then mix the cationic aluminum salt aqueous solution and the sodium metaaluminate aqueous solution, and react in an ultrasonic reactor for 2 - 3 h, filter and wash to obtain aluminum hydroxide precipitate. Then put the aluminum hydroxide precipitate into the polyethylene glycol aqueous solution, disperse it in an ultrasonic reactor for 1 - 2 h, stand and age for 5 - 7 h, filter, wash and dry to obtain an aluminum hydroxide precursor, wherein the mass ratio of the cationic aluminum salt, sodium metaaluminate, polyethylene glycol and deionized water is 1 - 3:4 - 6:0.4 - 0.6:60 - 70; In the above reaction process, in the present invention, the double hydrolysis of the cationic aluminum salt and sodium metaaluminate is used to obtain aluminum hydroxide precipitate. In order to accelerate the double hydrolysis process and make the reaction more complete, ultrasonic treatment is added in the present invention: because the double hydrolysis reaction is an endothermic process, ultrasonic treatment increases the temperature of the reaction solution and promotes the forward progress of the double hydrolysis reaction; in addition, the generated aluminum hydroxide precipitate is prone to aggregation, which will affect the subsequent silica coating process. Therefore, in the present invention, the common action of ultrasonic treatment and polyethylene glycol is used to obtain an aluminum hydroxide precursor with good dispersibility, and polyethylene glycol also acts as a pore-expanding agent; Step A2: Dissolve ammonia water and aluminum hydroxide precursor in an ethanol solution to obtain a precursor solution; put magnesium chloride hexahydrate into the precursor solution, stir magnetically for 16 - 20 h, age, and dry to obtain a core-shell aluminum hydroxide precursor-magnesium hydroxide, wherein the weight fraction of the ethanol solution is 28 - 32%, and the mass ratio of ammonia water, aluminum hydroxide precursor, and ethanol solution is 110 - 120:10 - 12:260 - 320; the mass ratio of magnesium chloride hexahydrate to the precursor solution is 8 - 12:210 - 230; Step A3: Dissolve tetraethyl orthosilicate in an ethanol solution, and then successively put ammonia water and the core-shell aluminum hydroxide precursor-magnesium hydroxide into the tetraethyl orthosilicate ethanol solution, stir magnetically for 16 - 20 h, centrifuge, wash, dry, and place it at 600 - 800 °C for roasting for 1.4 - 2.0 h, grind, and sieve to obtain functionalized alumina powder, wherein the mass ratio of tetraethyl orthosilicate, ethanol solution, ammonia water, and the core-shell aluminum hydroxide precursor-magnesium hydroxide is 2 - 4:260 - 340:80 - 100:10 - 12, the weight fraction of the ethanol solution is 32 - 36%. During the above reaction process, magnesium chloride hexahydrate undergoes a hydrolysis and condensation reaction on the surface of the aluminum hydroxide precursor, thereby obtaining a core-shell aluminum hydroxide precursor-magnesium hydroxide with the aluminum hydroxide precursor as the core and magnesium hydroxide as the shell. The aluminum hydroxide precursor will dehydrate to form activated alumina after subsequent high-temperature calcination, thereby coating a layer of magnesium oxide on the surface of the activated alumina. Magnesium oxide can effectively fill the cation vacancies on the surface of the activated alumina γ - A12O3, inhibit ion diffusion, and at the same time because Mg 2+ and A1 3+ have similar ionic radii, Mg 2+ can replace γ - A12O3 in the tetrahedral position in γ - A12O3, and the Si atoms entering the crystal lattice of γ - A12O3 block the structural rearrangement of γ - A12O3, thereby inhibiting the nucleation of α - A12O3 and improving the thermal stability of γ - A12O3.
[0010] Preferably, in the step A1, the cationic aluminum salt is at least one of aluminum nitrate, aluminum chloride, and aluminum sulfate.
[0011] In summary, the present application has the following beneficial effects: In order to improve the mechanical properties and thermal shock stability of the prepared refractory material, the present application starts from two aspects. One is to add functionalized alumina powder. The functionalized alumina powder consists of a three-layer structure. Its innermost core is alumina, the second outermost layer is magnesia, and the outermost layer is silica. In the initial stage of roasting, the aluminum powder forms a protective shell of aluminum nitride or alumina on its surface through low-temperature nitridation treatment (550 - 660 °C) in a nitrogen atmosphere. During the roasting process in a high-temperature nitrogen environment, the alumina in the core of the functionalized alumina powder can undergo a solid-phase reaction with the magnesia in the second outermost layer to form MgAlON. The silica in the outer layer can not only penetrate into the microstructure of MgAlON to form a spatial network structure, reducing the pore size while improving the slag and iron penetration resistance and mechanical strength of the refractory material, but also the SiOH on its surface has a hydrogen bond interaction with the oxygen generated by the high-temperature decomposition of magnesia, resulting in a lower oxygen partial pressure. At high temperatures, metallic Al is transformed into Al(g), and N2(g), Mg(g), and O2(g) react to form plate-like MgAlON, improving the mechanical properties, slag and iron penetration resistance, and thermal shock stability of the refractory material. The other is to add a modified binder. The modified binder is a blend of magnesium aluminate sol and aluminum phosphate. The modified binder obtained through compounding can not only form MgAlON but also form a dense magnesium aluminum phosphate ceramic phase under high-temperature roasting, which can significantly reduce the porosity. Introducing it into the composite corundum-based refractory material can synergistically act with the functionalized alumina powder to jointly improve the mechanical properties, slag and iron penetration resistance, and thermal shock stability of the refractory material. Detailed implementation manners
[0012] The following further elaborates on the present application with reference to examples.
[0013] Preparation Examples 1 - 3 and Comparative Preparation Examples 1 - 3 provide a kind of functionalized alumina powder.
[0014] Preparation Example 1 This preparation example provides a kind of functionalized alumina powder, which is prepared by the following steps: Step A1: Dissolve aluminum chloride hexahydrate, sodium metaaluminate, and polyethylene glycol with a molecular weight of 1000 in equal masses of deionized water respectively, stir at a rotation speed of 600 rpm for 0.5 h to obtain an aluminum chloride hexahydrate aqueous solution, a sodium metaaluminate aqueous solution, and a polyethylene glycol aqueous solution. Then mix the aluminum chloride hexahydrate aqueous solution and the sodium metaaluminate aqueous solution, and react at room temperature for 2 h under an ultrasonic frequency of 35 kHz and an ultrasonic power of 500 w. Filter and wash with deionized water 3 times to obtain aluminum hydroxide precipitate. Then put the aluminum hydroxide precipitate into the polyethylene glycol aqueous solution, and disperse it ultrasonically at an ultrasonic frequency of 30 kHz and an ultrasonic power of 450 w for 1 h, stand for aging for 5 h, filter and wash with deionized water 3 times, and dry at 90 °C to constant weight to obtain an aluminum hydroxide precursor. Among them, the mass ratio of aluminum chloride hexahydrate, sodium metaaluminate, polyethylene glycol, and deionized water is 1:4:0.4:60; Step A2: Dissolve ammonia water and the aluminum hydroxide precursor in an ethanol solution to obtain a precursor solution; put magnesium chloride hexahydrate into the precursor solution, stir at a rotation speed of 500 rpm for 16 h, age, and dry at 70 °C to constant weight to obtain a core-shell aluminum hydroxide precursor-magnesium hydroxide. Among them, the mass ratio of ammonia water, the aluminum hydroxide precursor, and the ethanol solution is 110:10:260; the mass ratio of magnesium chloride hexahydrate and the precursor solution is 8:210, and the weight fraction of the ethanol solution is 28%; Step A3: Dissolve tetraethyl orthosilicate in an ethanol solution, and then put ammonia water and the core-shell aluminum hydroxide precursor-magnesium hydroxide into the tetraethyl orthosilicate ethanol solution in sequence, stir magnetically for 16 h, centrifuge, wash with absolute ethanol and deionized water 3 times respectively, dry at 80 °C to constant weight, place it at 600 °C, calcine for 1.4 h, grind, and pass through a 100-mesh sieve to obtain functionalized alumina powder. Among them, the mass ratio of tetraethyl orthosilicate, the ethanol solution, ammonia water, and the core-shell aluminum hydroxide precursor-magnesium hydroxide is 2:260:80:10, and the weight fraction of the ethanol solution is 32%.
[0015] Preparation Example 2 This preparation example provides a kind of functionalized alumina powder, and this functionalized alumina powder is prepared by the following steps: Step A1: Dissolve aluminum nitrate nonahydrate, sodium aluminate, and polyethylene glycol with a molecular weight of 1000 in equal masses of deionized water respectively. Stir at a speed of 650 rpm for 0.75 h to obtain an aluminum nitrate nonahydrate aqueous solution, a sodium aluminate aqueous solution, and a polyethylene glycol aqueous solution. Then mix the aluminum nitrate nonahydrate aqueous solution and the sodium aluminate aqueous solution, and react at room temperature for 2.5 h under an ultrasonic frequency of 40 kHz and an ultrasonic power of 550 w. Filter and wash 4 times with deionized water to obtain aluminum hydroxide precipitate. Then put the aluminum hydroxide precipitate into the polyethylene glycol aqueous solution, and under an ultrasonic frequency of 35 kHz and an ultrasonic power of 500 w, ultrasonically disperse for 1.5 h, stand for aging for 6 h, filter, wash 4 times with deionized water, and dry at 95 °C to constant weight to obtain an aluminum hydroxide precursor. Among them, the mass ratio of aluminum nitrate nonahydrate, sodium aluminate, polyethylene glycol, and deionized water is 2:5:0.5:65; Step A2: Dissolve ammonia water and the aluminum hydroxide precursor in an ethanol solution to obtain a precursor solution; put magnesium chloride hexahydrate into the precursor solution, stir at a speed of 520 rpm for 18 h, age, and dry at 75 °C to constant weight to obtain a core-shell aluminum hydroxide precursor-magnesium hydroxide. Among them, the mass ratio of ammonia water, the aluminum hydroxide precursor, and the ethanol solution is 115:11:290; the mass ratio of magnesium chloride hexahydrate and the precursor solution is 10:220, and the weight fraction of the ethanol solution is 30%; Step A3: Dissolve tetraethyl orthosilicate in an ethanol solution, and then successively put ammonia water and the core-shell aluminum hydroxide precursor-magnesium hydroxide into the tetraethyl orthosilicate ethanol solution, stir magnetically for 18 h, centrifuge, wash 4 times with absolute ethanol and deionized water successively, dry at 85 °C to constant weight, place at 700 °C, calcine for 1.7 h, grind, and pass through a 150-mesh sieve to obtain functionalized alumina powder. Among them, the mass ratio of tetraethyl orthosilicate, the ethanol solution, ammonia water, and the core-shell aluminum hydroxide precursor-magnesium hydroxide is 3:300:90:11, and the weight fraction of the ethanol solution is 34%.
[0016] Preparation Example 3 This preparation example provides a kind of functionalized alumina powder, which is prepared by the following steps: Step A1: Dissolve aluminum sulfate octadecahydrate, sodium metaaluminate, and polyethylene glycol with a molecular weight of 1000 in equal masses of deionized water respectively, and stir for 1 h at a rotation speed of 700 rpm to obtain an aluminum sulfate octadecahydrate aqueous solution, a sodium metaaluminate aqueous solution, and a polyethylene glycol aqueous solution; then mix the aluminum sulfate octadecahydrate aqueous solution and the sodium metaaluminate aqueous solution, and react at room temperature for 3 h under an ultrasonic frequency of 45 kHz and an ultrasonic power of 600 w, filter, and wash with deionized water 5 times to obtain aluminum hydroxide precipitate. Then put the aluminum hydroxide precipitate into the polyethylene glycol aqueous solution, and disperse it ultrasonically for 2 h under an ultrasonic frequency of 45 kHz and an ultrasonic power of 550 w, stand for aging for 7 h, filter, and wash with deionized water 5 times, and dry at 100 °C to constant weight to obtain an aluminum hydroxide precursor, where the mass ratio of aluminum sulfate octadecahydrate, sodium metaaluminate, polyethylene glycol, and deionized water is 3:6:0.6:70; Step A2: Dissolve ammonia water and the aluminum hydroxide precursor in an ethanol solution to obtain a precursor solution; put magnesium chloride hexahydrate into the precursor solution, stir at a rotation speed of 540 rpm for 20 h, age, and dry at 80 °C to constant weight to obtain a core-shell aluminum hydroxide precursor-magnesium hydroxide, where the mass ratio of ammonia water, the aluminum hydroxide precursor, and the ethanol solution is 120:12:320; the mass ratio of magnesium chloride hexahydrate and the precursor solution is 12:230, and the weight fraction of the ethanol solution is 32%; Step A3: Dissolve tetraethyl orthosilicate in an ethanol solution, and then put ammonia water and the core-shell aluminum hydroxide precursor-magnesium hydroxide into the tetraethyl orthosilicate ethanol solution in turn, stir magnetically for 20 h, centrifuge, wash with absolute ethanol and deionized water 5 times in turn, dry at 90 °C to constant weight, place at 800 °C, calcine for 2.0 h, grind, and pass through a 200-mesh sieve to obtain functionalized alumina powder, where the mass ratio of tetraethyl orthosilicate, the ethanol solution, ammonia water, and the core-shell aluminum hydroxide precursor-magnesium hydroxide is 4:340:100:12, and the weight fraction of the ethanol solution is 36%.
[0017] Comparative Preparation Example 1 Comparative Preparation Example 1 is the same as Preparation Example 1, the only difference being that polyethylene glycol in Step A1 is replaced by deionized water.
[0018] Comparative Preparation Example 2 Comparative Preparation Example 2 is the same as Preparation Example 1, the only difference being that magnesium chloride hexahydrate in Step A2 is replaced by aluminum chloride hexahydrate.
[0019] Comparative Preparation Example 3 Comparative Example 3 is the same as Preparation Example 1, the only difference being that the tetraethyl orthosilicate ethanol solution in Step A3 is replaced by an ethanol solution.
[0020] Examples 1-3 and Comparative Examples 1-5 provide a preparation method of an Al@AlN-coated structure composite corundum-based refractory for RH refining furnaces.
[0021] Example 1 This example provides an Al@AlN-coated composite corundum-based refractory material for RH refining furnaces. The Al@AlN-coated composite corundum-based refractory material for RH refining furnaces is prepared by the following steps: Mix the aggregate, matrix and modified binder at a rotation speed of 300 rpm for 30 min until uniform, then continue to knead for 30 min, dry press and form under a 500 t press, then place the brick blank in an oven at 90 °C and dry for 16 h, then put it into a high-temperature furnace with a nitrogen atmosphere, keep it at 550 °C for 8 h, keep it at a sintering temperature of 1560 °C for 5 h, and wait for the furnace temperature to drop to room temperature to obtain the Al@AlN-coated composite corundum-based refractory material for RH refining furnaces. Among them, the mass ratio of the aggregate, matrix and modified binder is 76:10:2. The weight fractions of the components of the aggregate are as follows: 15% of 5-3 mm magnesia-alumina spinel particles, 48% of 3-1 mm magnesia-alumina spinel particles, and the balance of 1-0 mm magnesia-alumina spinel particles. The matrix includes functionalized alumina powder with a weight fraction of 52%, aluminum nitride powder with a weight fraction of 12%, the particle size of the aluminum nitride powder ≤ 72 µm, and the balance of metallic aluminum powder. The particle size of the metallic aluminum powder < 65 µm, and the A1 content in the metallic aluminum powder is 99%. The modified binder is composed of magnesium aluminate sol and aluminum phosphate mixed in a mass ratio of 3:1.
[0022] Example 2 This example provides an Al@AlN-coated composite corundum-based refractory material for RH refining furnaces. The Al@AlN-coated composite corundum-based refractory material for RH refining furnaces is prepared by the following steps: Mix the aggregate, matrix and modified binder at a rotation speed of 400 rpm for 25 min until uniform, then continue to knead for 30 min, dry press and form under a 550 t press, then place the brick blank in an oven at 95 °C and dry for 14 h, then put it into a high-temperature furnace with a nitrogen atmosphere, keep it at 605 °C for 4 h, keep it at a sintering temperature of 1620 °C for 4 h, and wait for the furnace temperature to drop to room temperature to obtain the Al@AlN-coated composite corundum-based refractory material for RH refining furnaces. Among them, the mass ratio of the aggregate, matrix and modified binder is 79:12:3. The weight fractions of the components of the aggregate are as follows: 24% of 5-3 mm magnesia-alumina spinel particles, 53.5% of 3-1 mm magnesia-alumina spinel particles, and the balance of 1-0 mm magnesia-alumina spinel particles; The matrix includes functionalized alumina powder with a weight fraction of 61%, aluminum nitride powder with a weight fraction of 18.5%, the particle size of the aluminum nitride powder ≤ 72 µm, and the balance of metallic aluminum powder. The particle size of the metallic aluminum powder < 65 µm, and the A1 content in the metallic aluminum powder is 99.5%. The modified binder is composed of magnesium aluminate sol and aluminum phosphate in a mass ratio of 3:1.5.
[0023] Example 3 This embodiment provides an Al@AlN-coated composite corundum-based refractory for RH refining furnace, which is prepared by the following steps: Mix the aggregate, matrix and modified binder at a rotation speed of 500 rpm for 25 minutes until uniform, then continue to knead for 30 minutes, dry press and form under a 600 t press, then place the brick blank in an oven at 100 °C and dry for 12 hours, then put it into a high-temperature furnace with a nitrogen atmosphere, keep it at 660 °C for 4 hours, keep it at a sintering temperature of 1680 °C for 3 hours, and wait for the furnace temperature to drop to room temperature to obtain the Al@AlN-coated composite corundum-based refractory for RH refining furnace. Among them, the mass ratio of the aggregate, matrix and modified binder is 82:14:4. The weight fractions of the components of the aggregate are as follows: 33% of 5-3 mm magnesia-alumina spinel particles, 59% of 3-1 mm magnesia-alumina spinel particles, and the balance of 1-0 mm magnesia-alumina spinel particles; the matrix includes 70% by weight of the functionalized alumina powder prepared in Preparation Example 3, 25% by weight of aluminum nitride powder, the particle size of the aluminum nitride powder ≤ 72 µm, and the balance of metallic aluminum powder, the particle size of the metallic aluminum powder < 65 µm, and the Al content in the metallic aluminum powder is 99.9%. The modified binder consists of magnesium aluminate sol and aluminum phosphate in a mass ratio of 3:2.
[0024] Comparative Example 1 Comparative Example 1 is the same as Example 1, except that the functionalized alumina powder in Example 1 is replaced by the functionalized alumina powder prepared in Comparative Preparation Example 1.
[0025] Comparative Example 2 Comparative Example 2 is the same as Example 1, except that the functionalized alumina powder in Example 1 is replaced by the functionalized alumina powder prepared in Comparative Preparation Example 2.
[0026] Comparative Example 3 Comparative Example 3 is the same as Example 1, except that the functionalized alumina powder in Example 1 is replaced by the functionalized alumina powder prepared in Comparative Preparation Example 3.
[0027] Comparative Example 4 Comparative Example 4 is the same as Example 1, except that the modified binder in Example 1 is replaced by magnesium aluminate sol.
[0028] Comparative Example 5 Comparative Example 5 is the same as Example 1, except that the modified binder in Example 1 is replaced by aluminum phosphate.
[0029] Performance Test Perform the following performance tests on the Al@AlN-coated composite corundum-based refractories prepared in Examples 1-3 and Comparative Examples 1-5: Cold crushing strength: Tested according to the refractory industry standard GB / T 3001-2017; Hot crushing strength: Tested according to the refractory industry standard GB / T 3002-2017, and the specific test conditions are 1400 °C for 0.5 h; Slag resistance test: Tested according to GB / T 8931-2007, and the erosion depth and erosion resistance are tested respectively, and obtained by the erosion test with molten high-temperature iron slag; Thermal shock resistance: Tested according to GB / T 17617-2018.
[0030] Table 1 Performance indexes of the Al@AlN-coated structure composite corundum-based refractory for RH refining furnace
[0031] It can be seen from the test data in Table 1 that the comprehensive performance of the Al@AlN-coated structure composite corundum-based refractory for RH refining furnace provided by the present invention is significantly better than that of the refractories prepared in Comparative Examples 1-5.
[0032] This specific embodiment is only an interpretation of the present application, and it is not a limitation of the present application. Those skilled in the art can make modifications without creative contributions to this embodiment according to needs after reading this specification, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. An Al@AlN coated structure composite corundum-based refractory for RH refining furnace, characterized in that, Prepared by the following steps: Using magnesium aluminate spinel as aggregate, and a mixture of functionalized alumina powder, aluminum nitride powder and metallic aluminum powder as matrix, adding a modified binder to the mixture of aggregate and matrix to obtain a raw material mixture, putting it into a high-temperature furnace under a nitrogen atmosphere, heating to 550 - 660 °C for heat preservation treatment for 4 - 8 h, then placing it at 1560 - 1680 °C for heat preservation for 3 - 5 h, and cooling to obtain an Al@AlN-coated structure composite corundum-based refractory material for RH refining furnace; The functionalized alumina powder is first prepared by double hydrolysis of a cationic aluminum salt and sodium aluminate to obtain aluminum hydroxide precipitate, then putting the aluminum hydroxide precipitate into polyethylene glycol, and performing ultrasonic dispersion to obtain an aluminum hydroxide precursor, then dissolving the aluminum hydroxide precursor and ammonia water, and then performing hydrolysis condensation with magnesium chloride hexahydrate to obtain a core-shell aluminum hydroxide precursor-magnesium hydroxide, and finally performing hydrolysis condensation with tetraethyl orthosilicate.
2. The Al@AlN coated structure composite corundum-based refractory material for RH refining furnace according to claim 1, characterized in that The magnesium aluminate spinel in the aggregate is one or a mixture of several of fused magnesium aluminate spinel, sintered magnesium aluminate spinel or high-purity magnesium aluminate spinel. The weight fractions of the components of the aggregate are as follows: 15 - 33% of 5 - 3 mm magnesium aluminate spinel particles, 48 - 59% of 3 - 1 mm magnesium aluminate spinel particles and the balance of 1 - 0 mm magnesium aluminate spinel particles.
3. The Al@AlN-coated structural composite corundum-based refractory material for RH refining furnace according to claim 1, characterized in that, The matrix includes functionalized alumina powder with a weight fraction of 52 - 70%, aluminum nitride powder with a weight fraction of 12 - 25%, the particle size of the aluminum nitride powder ≤ 72 µm and the balance of metallic aluminum powder, the particle size of the metallic aluminum powder < 65 µm, and the Al content in the metallic aluminum powder is 99 - 99.9%.
4. The Al@AlN-coated composite corundum-based refractory material for RH refining furnace according to claim 1, characterized in that, The functionalized alumina powder is prepared by the following steps: Step A1: Dissolve the cationic aluminum salt, sodium aluminate and polyethylene glycol in deionized water of equal mass respectively, and perform magnetic stirring for 0.5 - 1 h to obtain a cationic aluminum salt aqueous solution, a sodium aluminate aqueous solution and a polyethylene glycol aqueous solution; then mix the cationic aluminum salt aqueous solution and the sodium aluminate aqueous solution, and react in an ultrasonic reactor for 2 - 3 h, filter and wash to obtain an aluminum hydroxide precipitate, then put the aluminum hydroxide precipitate into the polyethylene glycol aqueous solution, disperse in an ultrasonic reactor for 1 - 2 h, stand for aging for 5 - 7 h, filter, wash and dry to obtain an aluminum hydroxide precursor; Step A2: Dissolve ammonia water and the aluminum hydroxide precursor in an ethanol solution to obtain a precursor solution; put magnesium chloride hexahydrate into the precursor solution, perform magnetic stirring for 16 - 20 h, age and dry to obtain a core-shell aluminum hydroxide precursor-magnesium hydroxide; Step A3: Dissolve tetraethyl orthosilicate in an ethanol solution, then put ammonia water and the core-shell aluminum hydroxide precursor-magnesium hydroxide into the tetraethyl orthosilicate ethanol solution in sequence, perform magnetic stirring for 16 - 20 h, centrifuge, wash and dry, place at 600 - 800 °C, calcine for 1.4 - 2.0 h, grind and sieve to obtain the functionalized alumina powder.
5. The Al@AlN-coated composite corundum-based refractory material for RH refining furnace according to claim 4, characterized in that, In the said Step A1, the mass ratio of the cationic aluminum salt, sodium aluminate, polyethylene glycol and deionized water is 1 - 3:4 - 6:0.4 - 0.6:60 - 70.
6. The Al@AlN-coated composite corundum-based refractory material for RH refining furnace according to claim 4, characterized in that, In the step A2, the mass ratio of ammonia water, aluminum hydroxide precursor and ethanol solution is 110-120:10-12:260-320; the mass ratio of magnesium chloride hexahydrate and precursor solution is 8-12:210-230, the weight fraction of ammonia water is 24-26%, and the weight fraction of ethanol solution is 28-32%.
7. The Al@AlN-coated structural composite corundum-based refractory material for RH refining furnace according to claim 4, characterized in that, In the step A3, the mass ratio of tetraethyl orthosilicate, ethanol solution, ammonia water and core-shell aluminum hydroxide precursor-magnesium hydroxide is 2-4:260-340:80-100:10-12, and the weight fraction of ethanol solution is 32-36%.
8. The Al@AlN-coated structure composite corundum-based refractory material for RH refining furnace according to claim 1, characterized in that, The modified binder is composed of magnesium aluminate sol and aluminum phosphate mixed in a mass ratio of 3:1-2.
9. The Al@AlN-coated structural composite corundum-based refractory material for RH refining furnace according to claim 1, characterized in that, The mass ratio of the aggregate, matrix and modified binder is 76-82:10-14:2-4.
Citation Information
Patent Citations
Aluminum-spinel-corundum composite refractory material and preparation method as well as application thereof
CN102627463A
Preparation method of electrostatic spinning colloidal liquid for preparation of aluminum oxide ultrafine fibers
CN103396100A
Corundum-magnesium aluminum spinelle-textured refractory aggregate with closed-hole structure and preparation method of refractory aggregate
CN103833383A
Preparation method of multi-morphology coexisting MgAlON refractory material for RH (Ruhrstahl Heraeus) refining furnace
CN114478030A
Materials formed by refractory grains bound in a matrix of aluminum nitride or sialon containing titanium nitride
US5925585A
Cited By
Anti-scouring ceramic composite magnesium-based refractory material and preparation method thereof
CN121895022A